2020
DOI: 10.1177/0363546520960108
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Force Development Remains Reduced in the Knee Flexors 3 to 9 Months After Anterior Cruciate Ligament Reconstruction Using Medial Hamstring Autografts: A Cross-Sectional Study

Abstract: Background: Anterior cruciate ligament (ACL) rupture is a serious injury with a high prevalence worldwide, and subsequent ACL reconstructions (ACLR) appear to be most commonly performed using hamstring-derived (semitendinosus tendon) autografts. Recovery of maximal muscle strength to ≥90% of the healthy contralateral limb is considered an important criterion for safe return to sports. However, the speed of developing muscular force (ie, the rate of force development [RFD]) is also important for the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…Analysis of the effects of sex on maximal and explosive strength following ACLR showed that males and females are typically affected similarly in the hamstrings but not in the quadriceps. This is in contrast to the results by Nielsen et al [ 30 ] who found significant effects of sex (female more impacted than males) in maximal and explosive hamstrings strength between 3 and 9 months following ACLR. An explanation for these differences could be the larger sample size, longer duration and the frequency and timing of testing throughout ACL rehabilitation (comparing early and late rehabilitation) in this study compared to their study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Analysis of the effects of sex on maximal and explosive strength following ACLR showed that males and females are typically affected similarly in the hamstrings but not in the quadriceps. This is in contrast to the results by Nielsen et al [ 30 ] who found significant effects of sex (female more impacted than males) in maximal and explosive hamstrings strength between 3 and 9 months following ACLR. An explanation for these differences could be the larger sample size, longer duration and the frequency and timing of testing throughout ACL rehabilitation (comparing early and late rehabilitation) in this study compared to their study.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the results of this study, patients who had ACLR with HT autografts would show maximal hamstrings strength recovery (≥ 90% LSI) during late rehabilitation period even while still having significant explosive hamstring strength asymmetry. Previous studies have also found explosive hamstring strength deficits between 3–9 months [ 30 ] and 9–12 months [ 31 ] following ACLR. However, these results were taken from only one assessment time point.…”
Section: Discussionmentioning
confidence: 99%
“…(Lehance et al, 2008) However, it has recently been suggested that explosive strength, i.e. the capacity to produce force/torque quickly during an explosive maximal voluntary contraction (MVC), is more representative of athletic performance as well as injury susceptibility (Padua et al, 2018; Suchomel et al, 2018; Zebis et al, 2011) and recovery (Jordan, Aagaard, & Herzog, 2015; Nielsen et al, 2020) than pure maximal strength. (Buckthorpe & Roi, 2017; Maffiuletti et al, 2016) Nowadays, the main index of explosive strength is represented by the rate of torque development (RTD), which is generally calculated as the slope of the torque‐time curve in distinct time intervals from contraction onset.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle power, for example, is a well-known determinant of physical function [11] and the phenomena of work- [12] and load- [13] induced muscle hypertrophy motivate tracking cumulative muscle work and force which may provide a basis for optimal exercise prescription and understanding subsequent dose-response relationships [14]. These analyses may be especially relevant for monitoring patients post-ACLR wherein the knee extensor and flexor musculature are compromised [15], [16] due to muscle atrophy [17] and muscle activation deficits [15]. In this case, early intervention is critical [18] and continuous, remote monitoring augments personalized rehabilitation for targeting specific biomechanical outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 17, 2021. ; https://doi.org/10.1101/2021.06. 16.448524 doi: bioRxiv preprint (which was not certified by peer review) is the author/funder. All rights reserved.…”
mentioning
confidence: 99%